Digitalization of Islamic Social Finance in Rural Areas: Optimizing the Management of Zakat, Infaq, and Sadaqah (ZIS) for Stunting Alleviation - Erwina Kartika Devi (CV. Civiliza Publishing, 2026)
Stunting in rural areas remains a crucial challenge for human resource development in Indonesia. Conversely, the potential of Islamic Social Finance through Zakat, Infaq, and Alms (ZIS) is immense, yet it is often hindered by traditional management practices and limited distribution reach. This study aims to explore how the digitalization of Islamic social finance can optimize ZIS management to support stunting reduction programs in rural settings. The methodology employed is a descriptive qualitative approach utilizing a literature study. The findings indicate that the implementation of digital platforms in the collection and distribution of ZIS can enhance transparency, accountability, and the precision of targeting nutritional aid for toddlers and education for pregnant women. Digitalization enables data integration between zakat management institutions (LAZ/BAZNAS) and village health data, ensuring that stunting interventions are conducted in a sustainable and measurable manner. In conclusion, the synergy between financial technology and Islamic philanthropic instruments serves as a strategic pillar in accelerating the decline of stunting rates while simultaneously improving the economic welfare of rural communities